THE EFFECT OF PROJECT-BASED FLIPPED LEARNING ON WRITING COMPETENCE OF THE ELEVENTH-GRADE STUDENTS OF SMA N 4 SINGARAJA IN ACADEMIC YEAR 2017/2018 - ., Kadek Ari Yuliani; ., Made Hery Santosa, S.Pd, M.Pd., Ph.D.; ., I Nyoman Pasek Hadi Saputra, S.Pd., M.Pd (Universitas Pendidikan Ganesha, 2017)
Penelitian ini memiliki tiga tujuan. Yang pertama adalah untuk menyelidiki tingkat kesiapan siswa kelas 11 SMA N 4 Singaraja terhadap pelaksanaan e-learning. Yang kedua adalah untuk mengetahui apakah ada perbedaan yang signifikan pada kompetensi menulis siswa kelas XI SMA N 4 Singaraja setelah menggunakan project based-flipped learning. Dan yang ketiga adalah mengamati persepsi siswa terhadap pelaksanaan pembelajaran project based-flipped learning. Metode penelitian yang digunakan adalah Explanatory Sequential Mix Method Design. Populasi adalah siswa kelas XI SMA N 4 Singaraja. Dua kelas digunakan sebagai sampel penelitian baik, dimana kelompok eksperiment diberikan pembelajaran berbasis project based-flipped learning dan kelompok control diberikan pembelajaran berbasis conventional teaching. Data kuantitatif yang dikumpulkan dalam penelitian ini dianalisis dengan menggunakan SPSS 22.0. Hasil analisis data menunjukkan bahwa siswa kelas XI SMA N 4 Singaraja siap melaksanakan pembelajaran berbasis e-learning. Selain itu, hasil analisis data kuantitatif menunjukkan bahwa kelompok eksperimen lebih baik daripada siswa dalam kelompok kontrol. Hal itu dibuktikan dengan hasil analisis statistik deskriptif yang menunjukkan skor rata-rata kelompok eksperimen yaitu 79,75 sedangkan skor rata-rata kelompok kontrol adalah 73,10. Hasil uji-t juga menunjukkan bahwa nilai t-observation (tobs) adalah 3,465 dan nilai t-critical value (tcv) adalah 2,024. Ini menunjukkan bahwa terdapat perbedaan yang signifikan pada kompetensi menulis siswa antara siswa yang diajar dengan menggunakan pembelajaran berbasis proyek dan siswa yang diajar dengan menggunakan media konvensional. Selain itu, hasil wawancara menunjukkan bahwa siswa memiliki persepsi positif terhadap pelaksanaan pembelajaran berbasis project-based flipped learning.Kata Kunci : Kesiapan terhadap penggunaan e-learning, pembelajaran berbasis project-based flipped learning, kompetensi menulis, persepsi terhadap project-based flipped learning. This present study had three aims. The first was to investigate the eleventh-grade students of SMA N 4 Singaraja readiness level of the implementation of e-learning. The second was to determine whether there is a significant difference on writing competence of the eleventh-grade students of SMA N 4 Singaraja after the implementation of Project based-flipped learning. And the third was to observe students’ perception toward the implementation of project-based flipped learning. The research design of this study was explanatory sequential mixed methods design. The population was the eleventh-grade students of SMA N 4 Singaraja. Two classes were used as the sample of this study. One class was assigned to the experimental group and treated by using project based-flipped learning. Meanwhile, the other class was assigned to the control group and treated by using conventional teaching. The quantitative data that collected in this study were analyzed by SPSS 22.0. The result of the data analysis showed that the eleventh-grade students of SMA N 4 Singaraja are ready for the implementation of e-learning. Besides, the result of the quantitative data analysis it showed the experimental group performed better than the students in control group. It was proven by the result of a descriptive statistical analysis that showed the mean score of the experimental group was 79.75 while the mean score of the control group was 73.10. The result of the t-test also showed that the value of t-observed (tobs) was 3.465 and the value of t-critical value (tcv) was 2.024. It showed that the value of tobs was higher than the value of tcv. Therefore, it can be concluded that there was a significant difference on students writing competency between students taught by using Project based-learning and students taught by using conventional media. In addition, the result of the interview showed that the students’ had a positive perception toward the implementation of project based-flipped learning.keyword : E-learning readiness, project-based flipped learning, writing competence, students’ perception of project-based flipped learning.